Hyaluronan-carnosine conjugates inhibit Aβ aggregation and toxicity - Greco, Valentina; Naletova, Irina; Ahmed, Ikhlas M. M.; Vaccaro, Susanna; Messina, Luciano; La Mendola, Diego; Bellia, Francesco; Sciuto, Sebastiano; Satriano, Cristina; Rizzarelli, Enrico (Scientific reports, 2020)
Alzheimer’s disease is the most common neurodegenerative disorder. Finding a pharmacological approach that cures and/or prevents the onset of this devastating disease represents an important challenge for researchers. According to the amyloid cascade hypothesis, increases in extracellular amyloid-β (Aβ) levels give rise to different aggregated species, such as protofibrils, fibrils and oligomers, with oligomers being the more toxic species for cells. Many efforts have recently been focused on multi-target ligands to address the multiple events that occur concurrently with toxic aggregation at the onset of the disease. Moreover, investigating the effect of endogenous compounds or a combination thereof is a promising approach to prevent the side effects of entirely synthetic drugs. In this work, we report the synthesis, structural characterization and Aβ antiaggregant ability of new derivatives of hyaluronic acid (Hy, 200 and 700 kDa) functionalized with carnosine (Car), a multi-functional natural dipeptide. The bioactive substances (HyCar) inhibit the formation of amyloid-type aggregates of Aβ 42 more than the parent compounds; this effect is proportional to Car loading. Furthermore, the HyCar derivatives are able to dissolve the amyloid fibrils and to reduce Aβ-induced toxicity in vitro. The enzymatic degradation of Aβ is also affected by the interaction with HyCar.